2021
DOI: 10.3390/life11040297
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Targeting Human MEK1/2 Enhances ERK and p38 Phosphorylation under Oxidative Stress or with Phenothiazines

Abstract: Small molecules are routinely used to inhibit protein kinases, but modulators capable of enhancing kinase activity are rare. We have previously shown that the small molecule INR119, designed as an inhibitor of MEK1/2, will enhance the activity of its fission yeast homologue, Wis1, under oxidative stress. To investigate the generality of these findings, we now study the effect of INR119 in human cells under similar conditions. Cells of the established breast cancer line MCF-7 were exposed to H2O2 or phenothiazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…CHOP induces the expression of GADD34 and increases levels of ERO1α, which results in the production of cytotoxic ROS [ 53 ]. As downstream signaling, the phosphorylation of JNK and other stress-related signaling molecules (ERK1/2 and p38) is in accordance with observed results from fluphenazine in MCF-7 breast cancer cells [ 54 , 55 ]. The knockdown of CHOP in K562 cells resulted in an attenuation of TR-promoted cytotoxicity, thereby demonstrating that ER stress contributes to TR-induced cell death.…”
Section: Discussionsupporting
confidence: 86%
“…CHOP induces the expression of GADD34 and increases levels of ERO1α, which results in the production of cytotoxic ROS [ 53 ]. As downstream signaling, the phosphorylation of JNK and other stress-related signaling molecules (ERK1/2 and p38) is in accordance with observed results from fluphenazine in MCF-7 breast cancer cells [ 54 , 55 ]. The knockdown of CHOP in K562 cells resulted in an attenuation of TR-promoted cytotoxicity, thereby demonstrating that ER stress contributes to TR-induced cell death.…”
Section: Discussionsupporting
confidence: 86%
“…Inhibitors targeting the SMAD-interacting enzymes such as AKT/PKB (Ser/Thr kinase/protein kinase B), CDK (cyclin-dependent kinase), GSK GSK3b (axin/glycogen synthase kinase 3 beta), and ERK (extracellular signal-related kinase) are cataloged in Table 1 [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. These inhibitors act by modulating the phosphorylation activity of the kinases and thereby regulate their interaction, the R-SMADs, and SMAD-mediated signaling in epithelial and mesenchymal cells.…”
Section: Activity and Nucleocytoplasmic Trafficking Of Smadsmentioning
confidence: 99%
“…Significant advancements have been observed in the area of small-molecule inhibitors of AKT functions through different mechanisms. In addition, pleckstrin homology domain, ATP-competitive, and allosteric inhibitors of AKT are noteworthy in developing clinical trials, and therapeutic benefits in treating different solid tumors have been observed [ 83 ]. A preclinical study of MK-2206 in epithelial morphology of pancreatic cancer cells by Wang et al [ 72 ] showed that AKT phosphorylation is inhibited, and cell proliferation is attenuated by the application of the MK-2206 inhibitor.…”
Section: Activity and Nucleocytoplasmic Trafficking Of Smadsmentioning
confidence: 99%
See 1 more Smart Citation